2022
DOI: 10.5194/acp-22-9461-2022
|View full text |Cite
|
Sign up to set email alerts
|

Iron (Fe) speciation in size-fractionated aerosol particles in the Pacific Ocean: The role of organic complexation of Fe with humic-like substances in controlling Fe solubility

Abstract: Abstract. Atmospheric deposition is one of the main sources of dissolved iron (Fe) in the ocean surfaces. Atmospheric processes are recognized as controlling fractional Fe solubility (Fesol%) in marine aerosol particles. However, the impact of these processes on Fesol% remains unclear. One of the reasons for this is the lack of field observations focusing on the relationship between Fesol% and Fe species in marine aerosol particles. In particular, the effects of organic ligands on Fesol% have not been thorough… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…A, although the anthropogenic emission of TMIs is accurately considered based on the latest emission data set, the modeled estimates of solubilities of anthropogenic and dust Fe and Mn remain highly uncertain in cloud water, as pointed out previously. 14 , 29 , 31 , 33 The increased Fe solubilities have been indicated based on global model comparisons with multiple field campaigns over the Northwest Pacific 57 and also observed toward the downstream region of East Asia, 58 , 59 mainly because fine mineral aerosols can be acidified due to air pollution. Thus, for Exp.…”
Section: Resultsmentioning
confidence: 99%
“…A, although the anthropogenic emission of TMIs is accurately considered based on the latest emission data set, the modeled estimates of solubilities of anthropogenic and dust Fe and Mn remain highly uncertain in cloud water, as pointed out previously. 14 , 29 , 31 , 33 The increased Fe solubilities have been indicated based on global model comparisons with multiple field campaigns over the Northwest Pacific 57 and also observed toward the downstream region of East Asia, 58 , 59 mainly because fine mineral aerosols can be acidified due to air pollution. Thus, for Exp.…”
Section: Resultsmentioning
confidence: 99%
“…9b). In addition, non-magnetic aluminosilicates of coal combustions and MSWI could not increase the EF of Fe in fine aerosol particles because the EF of Fe in these ashes was almost 1 (Sakata et al, 2022;Li et al, 2022). Therefore, non-magnetic aluminosilicates derived from coal combustion and MSWI were unlikely the dominant source of aerosol particles with high Fesol% and [d-Fe]/[d-Al] ratios.…”
Section: The [D-fe]/[d-al] Ratio Of Non-crustal Fe: Non-magnetic Frac...mentioning
confidence: 99%
“…6e and 6f). Enrichment of d-Fe and d-Al in size-fractionated aerosol samples has been reported not only in the urban atmosphere (Fang et al, 2017;Hsieh et al, 2022) but also in the marine atmosphere (McDaniel et al, 2019;Baker et al, 2020;Sakata et al, 2022). These previous studies have reported that the higher d-Fe and d-Al in coarse aerosol particles were caused by either or both (i) contamination of anthropogenic aerosol with high Fesol% and Alsol% and (ii) solubilization of Fe and Al in fine aerosol particles by atmospheric processes.…”
Section: Size-distributions Of D-fe and D-al Concentration And Their ...mentioning
confidence: 99%
See 2 more Smart Citations